2016
DOI: 10.1101/088682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivoimaging of coral tissue and skeleton with optical coherence tomography

Abstract: statement: We use optical coherence tomography to study the microstructural properties of coral tissues and skeletons.OCT imaging of corals Abstract Optical coherence tomography (OCT) is a non-invasive three-dimensional imaging technique with micrometer resolution allowing microstructural characterization of tissues in vivo and in real time. We present the first application of OCT for in vivo imaging of tissue and skeleton structure of intact living corals spanning a variety of morphologies and tissue thicknes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 82 publications
7
34
0
Order By: Relevance
“…In spite of this difference in overall acclimation to light, a decrease in the surface layer photosynthesis was seen in the coral sediment at an incident irradiance of 500 μmol photons m −2 s −1 , which could either reflect the heterogeneity and patchiness of the phototrophs found in the sediment, or could point to a possible migration of motile phototrophic organisms. Migration as a phototactic response is recognized as an effective mechanism for controlling photon absorption across different systems such as terrestrial plants (Wada et al, 2003) and microphytobenthic assemblages (Serodio et al, 2006; Cartaxana et al, 2016a,b), and similar phototactic response has been shown in coral tissues where the in hospite light environment can be modulated by host tissue movement (Wangpraseurt et al, 2014a, 2017). Downward migration at high irradiances is probably correlated with increasing photic stress e.g., by the formation of reactive oxygen species that can damage photosystem II by preventing the synthesis of the D1 protein in these layers (Hihara et al, 2001; Nishiyama et al, 2001; Aarti et al, 2007; Latifi et al, 2009; Al-Najjar et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In spite of this difference in overall acclimation to light, a decrease in the surface layer photosynthesis was seen in the coral sediment at an incident irradiance of 500 μmol photons m −2 s −1 , which could either reflect the heterogeneity and patchiness of the phototrophs found in the sediment, or could point to a possible migration of motile phototrophic organisms. Migration as a phototactic response is recognized as an effective mechanism for controlling photon absorption across different systems such as terrestrial plants (Wada et al, 2003) and microphytobenthic assemblages (Serodio et al, 2006; Cartaxana et al, 2016a,b), and similar phototactic response has been shown in coral tissues where the in hospite light environment can be modulated by host tissue movement (Wangpraseurt et al, 2014a, 2017). Downward migration at high irradiances is probably correlated with increasing photic stress e.g., by the formation of reactive oxygen species that can damage photosystem II by preventing the synthesis of the D1 protein in these layers (Hihara et al, 2001; Nishiyama et al, 2001; Aarti et al, 2007; Latifi et al, 2009; Al-Najjar et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Although, P. damicornis does also have a GFP-like pigment (Takabayashi and Hoegh-Guldberg, 1995), the GFP-like pigments in Favites sp. are arranged in a chromatophore system that strongly enhances light scattering (Lyndby et al, 2016; Wangpraseurt et al, 2016b) facilitating a steep light attenuation along the enhanced optical path within thick scattering coral tissue (Wangpraseurt et al, 2012; Lyndby et al, 2016). Our finding of low light levels in the aboral polyp tissues therefore suggests that tissue background scattering and absorption effectively attenuate light even in bleached tissues of Favites sp.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors knowledge there is only the publication of Wangpraseurt et al (bioRxiv) who introduced this approach describing the expansion and compaction of coral tissue. A change of the surface area by a factor of two was determined.…”
Section: Oct In Biofilm Researchmentioning
confidence: 99%